Advances in Molecular Genetics of Brain Tumors - Pećina-Šlaus, Nives; Jovčevska, Ivana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint encompasses a number of articles that focus on the molecular blueprint of brain tumors. A collection of relevant papers in the rapidly expanding field of brain tumor molecular genetics broadens our knowledge about the biology of brain tumors, and inspires further studies that will improve the diagnosis and clinical management of brain tumors. Due to the great heterogeneity of brain tumors it is important to research and understand every aspect of their initiation, progression and metastasis in order to design better diagnostic and therapeutic approaches for their clinical management and patient benefit.